2004
DOI: 10.1021/ic0492688
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Hydrazone Ligands as Nucleophiles:  Reactions of Fe(papy)2

Abstract: The diamagnetic iron(II) complexes of the hydrazone ligand pyridinecarboxaldehyde-2‘-pyridylhydrazone (papyH) have been characterized by NMR, IR, UV−vis, and electrochemistry. The dication Fe(papyH)2 2+ undergoes reversible one-electron oxidation at 0.66 V vs internal ferrocene and shows a strong metal−ligand charge-transfer band in the visible region at 524 nm. Deprotonation with NaOH gives diamagnetic, neutral Fe(papy)2 with an oxidation potential of −0.25 V vs internal ferrocene and a charge-transfer band a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…[46] Ligand exchange reactions employing metal halide or pseudo-halide precursors are known to lead preferably to complexes of the type metal/ligand = 1:1, [19][20][21][22] whereas employing precursors with noncoordinating counterions leads to complexes of the type 2:1. [18,[24][25][26] Nitrate precursors seem to exhibit reactivity at the borderline, enabling both stoichiometries. Thus, fine-tuning of electronic and steric properties on the pyridazine ring results in two different metal-to-ligand ratios.…”
Section: Solid State Structures Of the Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…[46] Ligand exchange reactions employing metal halide or pseudo-halide precursors are known to lead preferably to complexes of the type metal/ligand = 1:1, [19][20][21][22] whereas employing precursors with noncoordinating counterions leads to complexes of the type 2:1. [18,[24][25][26] Nitrate precursors seem to exhibit reactivity at the borderline, enabling both stoichiometries. Thus, fine-tuning of electronic and steric properties on the pyridazine ring results in two different metal-to-ligand ratios.…”
Section: Solid State Structures Of the Complexesmentioning
confidence: 99%
“…Methylation of the nitrogen atom seemed to be a viable solution without changing the spectroscopic properties of the complexes. [25] These methylated derivatives recently experienced a renaissance as the key building blocks in forming self-assembled morphologies. Complex grid-and rack-type constructions [26][27][28] are induced by dynamic structural and conformational changes of the ligand backbone as described by Lehn and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the hydrazones have been drawing much attention from coordination chemists, because of the strong tendency of aroyl hydrazones to chelate transition metals [20 -25], lanthanides [26,27], and main group metals [28,29]. It has also been suggested that nucleophilic substitution [30] of hydrazone ligands may be an important route to assemble nanoscale molecular clusters. Qi and Wang [31] have reported the preparation of novel dendritic mixed-valence ruthenium complexes, which can act as variable attenuators for the control of optical signals.…”
Section: Introductionmentioning
confidence: 99%
“…All the complexes were characterized by elemental analyses, stoichiometric studies, FTIR, absorption and emission spectroscopy. In [Pd(L)Cl] the ligand in its anionic form coordinates in a tridentate manner through pyridyl-N, quinoline-N and distal-N of the hydrazine residue [15,20] (Scheme 1)…”
Section: Resultsmentioning
confidence: 99%